Estructura diamétrica y carbono almacenado en las especies comerciales de un bosque de colina baja de la concesión forestal n° 16-LOR-MAY/CON-MAD-2019-009 del distrito de Mazán, Loreto. 2021 - Alvan Linares, Carlos Enrique (2022)
The diametric structure and the carbon stored in the commercial species of a low-hill forest of the Mazán district, Loreto, Peru were quantified. The data from the forest census of the commercial species of the operational plan (PO) 1 of the felling plot (PC) 6 of the forest concession contract 16-LOR-MAY / CON-MAD-2019-009 for timber purposes was evaluated. The distribution of the number of trees by diameter class reports 3,39 trees/ha (8120 trees), where R. cruegeri (0.58 trees/ha, 1396 trees), A. loretensis (0,58 trees/ha, 1392 trees) and V. lomatophylla (0,29 trees/ha, 692 trees) contain the highest number of trees; while D. micrantha (0,03 trees/ha, 67 trees) and A. giganteum (0,02 trees/ha, 57 trees) contain the lowest number of trees. The carbon stored amounts to 11,50 tC/ha (27 523,90 tC), where A. loretensis (2,08 tC/ha, 4975,49 tC), R. cruegeri (1,72 tC/ha, 4111,98 tC), B. macrophylla (1,37 tC/ha, 3269,68 tC) and V. lomatophylla (0,88 tC/ha, 2117,31 tC), report higher values; while D. micrantha (0,13 tC/ha, 315,54 tC), A. giganteum (0,12 tC/ha, 296,29 tC) and O. glycycarpa (0,08 tC/ha, 179,98 tC) report lower values.